The efficacy and safety of Chinese herbal medicine as an add-on therapy for type 2 diabetes mellitus patients with carotid atherosclerosis: An updated meta-analysis of 27 randomized controlled trials - Zhang, Zehua; Leng, Yulin; Chen, Zhengtao; Fu, Xiaoxu; Liang, Qingzhi; Peng, Xi; Xie, Hongyan; Gao, Hong; Xie, Chunguang (Frontiers in Pharmacology, 2023)
Background: Type 2 diabetes mellitus is a clinical metabolic syndrome characterized by persistent hyperglycemia. Patients with T2DM are more likely to have carotid atherosclerosis, which can lead to dizziness, amaurosis or even stroke. Chinese herbal medicine has shown possible efficacy and safety in treating T2DM with CAS. However, the existing evidence was not robust enough and the results were out of date. Objective: This meta-analysis aimed to summarize the latest evidence and systematically evaluate the clinical efficacy and safety of CHM in treating T2DM with CAS, providing a reference for subsequent research and clinical practice. Methods: Both Chinese and English databases were searched from their inceptions to July 2022. Randomized controlled trials using oral CHM to treat T2DM with CAS were included. The literature quality was assessed using the risk of bias assessment tool in the Cochrane Handbook. Data extraction was conducted on the selected studies. Review Manager 5.4 and Stata 16.0 were used for meta-analysis. Sources of heterogeneity were explored by meta-regression or subgroup analysis. Funnel plot and Egger's test were used to assess publication bias and the evidence quality was assessed by GRADE. Results: 27 eligible studies, involving 2638 patients, were included in this study. Results showed that compared with western medicine, combined with CHM was significantly better in improving CIMT, carotid plaque Crouse score, TC, TG, LDL-C, HDL-C, HbA1c, FBG, 2hPG, HOMA-IR and HOMA-β. Due to the small number of included studies, it is unclear whether CHM has an improving effect on NO, ET-1, PSV and RI. No serious adverse events were observed. Conclusions: Based on this meta-analysis, we found that in the treatment of T2DM with CAS, combined with CHM has more advantages than WM alone, which can further reduce CIMT and carotid plaque Crouse score, regulate glucose and lipid metabolism, improve insulin resistance and enhance islet β-cell function. Meanwhile, CHM is relatively safe. However, limited by the quality of included studies and herbal heterogeneity, the efficacy and safety of CHM remain uncertain. More high-quality studies are still needed to provide more reliable evidence for the clinical application of CHM.